Joint Information Acquisition and New Technology Adoption: Late Versus Early Adoption - Wozniak, Gregory D. (The Review of Economics and Statistics, 1993)
The objective of this paper is to examine empirically the determinants of the joint decision whether or not to adopt a new input and invest in technical knowledge. A log-linear probability model of the joint occurrence or nonoccurrence of adoption and information acquisition is estimated. The results suggest that information acquisition and adoption decisions are made jointly and that the influences of the determinants of adoption and information acquisition differ with the timing of adoption and the channels of information dissemination. Copyright 1993 by MIT Press.